Young children take an interest in the newspaper if they see their parents reading it (Journal of Parents and Teachers, 2026)
The family plays a vital role in encouraging reading; this article describes the newspaper as an educational tool that is excellent for use at home. Children develop a greater interest in current affairs and news when they see their parents reading regularly.
Keywords: The press; family; reading; practical activities; holistic